Organizational Change and Justice - Janelle E. Wells; Nefertiti A. Walker (University of Kansas Libraries, 2016)
In the sport industry, one thing that is constant is change. Since numerous forces may drive and guide the change process, the goal of this study was to examine ethical leadership, transparency, and organizational justice during an organizational change of a consolidating National Collegiate Athletic Association (NCAA) Division I men's and women's athletic department. Framed from the organizational change, ethical leadership, and organizational justice literature, this qualitative case study included interviews from nine university stakeholders and analysis of public documents published over the last decade. Results revealed transparent ethical leaders in an instrumental climate espoused positive organizational justice perceptions. In addition, employees' perceptions of transparent ethical leaders and positive organizational justice helped champion favorable responses to the organizational change. Implications of this research include encouraging intercollegiate athletic administrators to consider the security and well-being of stakeholders, which helps garner favorable responses during an organizational change.